The integrity of the personality. - "Storr, Anthony." ("Middlesex, Eng. c1963.", 1981)
This book explain the draws on various approaches to psychotherapy to discuss basic assumptions about human nature, the goals of the therapeutic process, and the development of the human personality.
Keywords: Psychology